A new giraffe ossicone from Wolf Camp, Tunggur Formation, Inner Mongolia suggests a new genus in Bohlinini (Artiodactyla, Giraffidae) - Xiaoming Wang; Nikos Solounias; Su-kuan Hou; Lu Li; Yukimitsu Tomida (PLoS ONE, 2025)
The classic Middle Miocene Wolf Camp locality discovered in 1930 by the Third Asiatic Expeditions of the American Museum of Natural History has been long known to produce an extinct giraffe, Palaeotragus tungurensis Colbert, 1936. Its dental and limb morphology offers tantalizing clues to a close relationship to the living giraffe, Giraffa. Its ossicone, a key part of the giraffe anatomy, is unknown since its initial description. Our discovery, in 2011, of an almost perfectly preserved ossicone from Wolf Camp thus fills this void and is described herein. Novel morphology of the ossicone, unlike any known so far, warrants a new generic name, Qilin, and Q. tungurensis adds important evidence that this Middle Miocene record from Inner Mongolia represents a key taxon in the evolution of the subfamily Giraffinae. Ossicone morphology is fundamentally similar to that of living Giraffa as well as members of Bohlinini. Dentally, Q. tungurensis also strongly supports its membership within Bohlinini with a unique shared derived character of P2-3 para- and metastyles bending inward to mesostyle. Q. tungurensis possesses a slender limb and a modestly deep trough on the posterior surface of the metacarpals that also suggest membership in Bohlinini. Combined with knowledge about its dental and limb morphology, the new Wolf Camp ossicone indicates an important stage of giraffine evolution, and contributes to a better understanding of its chronology and zoogeography.